1993
DOI: 10.3109/10715769309147496
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Human Recombinant Manganese Superoxide Dismutase in Models of Inflammation

Abstract: We evaluated a novel human recombinant preparation of manganese superoxide dismutase (MnSOD) for anti-inflammatory and anti-oxidant activity compared with a copper zinc (CuZn) SOD preparation. The results showed that administration of MnSOD (50, 100 and 200 micrograms kg-1) in the Freund's Complete Adjuvant (FCA) mediated paw oedema model suppressed the inflammation at 4 hours by 43, 25 and 43% (P < 0.001, P < 0.01 and P < 0.001 at respective doses). However, 24 hours post-challenge, MnSOD (50 and 100 microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…13,21 In rat adjuvant-induced foot pad oedema, administration of human recombinant MnSOD resulted in a reduction of paw swelling. 21 In a different model, antigen-induced arthritis in the mouse, amidated catalase suppressed the inflammatory response, whereas SOD had no effect. 13 It appears that superoxide radicals and hydrogen peroxide might exert different effects on the different animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,21 In rat adjuvant-induced foot pad oedema, administration of human recombinant MnSOD resulted in a reduction of paw swelling. 21 In a different model, antigen-induced arthritis in the mouse, amidated catalase suppressed the inflammatory response, whereas SOD had no effect. 13 It appears that superoxide radicals and hydrogen peroxide might exert different effects on the different animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Rats that received cells overexpressing EC-SOD at a higher density of 1 Â 10 5 / joint did not show any effect compared with the control animals. It has been reported 21 that in the adjuvantinduced foot pad oedema model, pretreatment with different doses of MnSOD resulted in a bell-shaped curve, in which very high doses of MnSOD caused a loss of protection. Recently, Liochev and Fridovich 25 reported that CuZnSOD, besides its superoxide dismutase activity, has a superoxide reductase activity.…”
Section: Antioxidant Gene Therapy For Arthritis L Dai Et Almentioning
confidence: 99%
“…It is also suggests that the inhibitory effect of PC-SOD on cellular infiltration may be partially due to the life extendency of NO. On the other hand, the dose-response curve for PC-SOD showed a bell-shape pattern, like free SOD (13,14). SOD produces H2O2 in the process of scavenging 02.…”
mentioning
confidence: 99%
“…Further limiting the application of native SOD is its proinflammatory effect at high doses (Dowling et al, 1993), mediated via Fenton-type reactions (Mao et al, 1993), although low doses may have an anti-inflammatory action. These factors may contribute to the conflicting results of early studies with native SOD treatment to attenuate O 2 .…”
mentioning
confidence: 99%